Retrospective cohort study of prognostic factors in patients with oral cavity and oropharyngeal squamous cell carcinoma. Issue 4 (16th June 2015) - Carrillo, José F.; Carrillo, Liliana C.; Cano, Ana; Ramirez–Ortega, Margarita C.; Chanona, Jorge G.; Avilés, Alejandro; Herrera–Goepfert, Roberto; Corona–Rivera, Jaime; Ochoa–Carrillo, Francisco J.; Oñate–Ocaña, Luis F.
Abstract: Background: Prognostic factors in oral cavity and oropharyngeal squamous cell carcinoma (SCC) are debated. The purpose of this study was to investigate the association of prognostic factors with oncologic outcomes. Methods: Patients with oral cavity and oropharyngeal SCC treated from 1997 to 2012 were included in this retrospective cohort study. Associations of prognostic factors with locoregional recurrence (LRR) or overall survival (OS) were analyzed using the logistic regression and the Cox models. Results: Six hundred thirty‐four patients were included in this study; tumor size, surgical margins, and N classification were associated with LRR ( p < .0001); considering histopathology: perineural invasion, lymphocytic infiltration, infiltrative borders, and N classification were significant determinants of LRR. Tumor size, N classification, alcoholism, and surgical margins were associated with OS ( p < .0001); considering pathologic prognostic factors, perivascular invasion, islands borders, and surgical margins were independently associated with OS ( p < .0001). Conclusion: Surgical margins, perineural and perivascular invasion, lymphocytic infiltration, and infiltrative patterns of tumor invasion are significant prognostic factors in oral cavity and oropharyngeal SCC. © 2015 Wiley Periodicals, Inc. Head Neck 38: 536–541, 2016